2010
DOI: 10.1111/j.1749-6632.2009.05339.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, socioeconomic status, and health: Complexities, ongoing challenges, and research opportunities

Abstract: This paper provides an overview of racial variations in health and shows that differences in socioeconomic status (SES) across racial groups are a major contributor to racial disparities in health. However, race reflects multiple dimensions of social inequality and individual and household indicators of SES capture relevant but limited aspects of this phenomenon. Research is needed that will comprehensively characterize the critical pathogenic features of social environments and identify how they combine with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,002
5
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,152 publications
(1,047 citation statements)
references
References 156 publications
28
1,002
5
12
Order By: Relevance
“…Further, SES measures such as educational attainment may not be commensurate between different racial groups [45], and individual-level SES measures do not capture neighborhood-and community-level socioeconomic and health environmental factors. For example, at the same level of income and education, Black populations are less wealthy and may live in environments such as food deserts that do not promote health [46]. In terms of child populations, Acevedo-Garcia and colleagues [47] found that 76 % of Black children live under worse conditions than the worst off White children (defined as being the 25 % percent living in the highest-poverty White neighborhoods).…”
Section: Discussionmentioning
confidence: 99%
“…Further, SES measures such as educational attainment may not be commensurate between different racial groups [45], and individual-level SES measures do not capture neighborhood-and community-level socioeconomic and health environmental factors. For example, at the same level of income and education, Black populations are less wealthy and may live in environments such as food deserts that do not promote health [46]. In terms of child populations, Acevedo-Garcia and colleagues [47] found that 76 % of Black children live under worse conditions than the worst off White children (defined as being the 25 % percent living in the highest-poverty White neighborhoods).…”
Section: Discussionmentioning
confidence: 99%
“…The physical impact of stressors may reflect coping patterns, the physiological accumulation of psychosocial stressors (i.e., 'wear and tear' on the body), or the indirect consequences of regularly confronting barriers to health-promoting factors, such as appropriate employment or adequate medical care (Williams et al, 2010). Stress is associated with obesity (Dallman et al, 2003), with at least one of the mechanisms being chronic inflammation in the body (Fuligni et al, 2009;Robles et al, 2005).…”
Section: Acculturative Stressorsmentioning
confidence: 99%
“…Largely separate literatures address racial and ethnic disparities and socioeconomic disparities. Studies that have data on both variables often use one as the control for the other and rarely consider how their joint functioning affects health or how each is entwined with other threats to good health (70). Health.…”
Section: Rigor and Vigor: Measurement Issuesmentioning
confidence: 99%